Pengaruh Penerapan Program Double track, Rasionalitas, dan Etika Bisnis terhadap Kesiapan Berwirausaha Siswa SMA Negeri 1 Turen - Yasmin Dwi Retno Utari; Annisya Annisya (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
The number of students not continuing to higher education remains high, which raises concerns regarding the availability of skilled human resources ready to enter the labor market. This condition highlights the importance of developing alternative pathways that can prepare students for both employment and entrepreneurship. This study aims to examine the influence of the double track program, rationality, and business ethics on the entrepreneurial readiness of students at SMA Negeri 1 Turen. The subjects of this research were students participating in the double track program at SMA Negeri 1 Turen during the 2023/2024 academic year. This study employed a quantitative approach with data collected through questionnaires. The data were analyzed to determine the effect of each variable on entrepreneurial readiness. The findings indicate that the double track program, rationality, and business ethics have a significant influence on students’ entrepreneurial readiness. The double track program provides students with opportunities to develop practical skills and competencies required to start and manage a business. Meanwhile, rationality supports logical decision-making, and business ethics guides students in conducting responsible and sustainable business practices. Overall, these three factors play an important role in shaping students’ readiness to become entrepreneurs in the future.